Efficiency of 1-on-1 play situations for high-level soccer players during the World and European championships in relation to position on the pitch and match time - Szwarc, A.; Radziminski, L.; Jastrzebski, Z.; Kromke, K. (International Journal of Sports Science & Coaching, 2017)
The aim of the study was to assess the efficiencies of players in 1-on-1 situations in terms of their position on the pitch and the match time during the final matches of the World Cup and European Championships from 1990 to 2014. The research was conducted on a sample of 1012 football players whose teams competed in the semi-finals, finals and the third place matches during the Football World Cup and European Championships from 1990 to 2014. The study included the performances of 506 players in 1-on-1 situations during 46 matches that were terminated at the regulation 90 min. The study revealed that during an average match, the players performed 231 times in 1-on-1 situations with 51% accuracy. The level of accuracy in 1-on-1 situations was significantly higher (p = 0.05) in winning teams than in losing teams particularly at the beginning of the game and in the middle zone of the pitch. Moreover, the results of our study showed that the highest effectiveness of the duels was noted in the defence zone and was decreasing along with moving the actions closer to the opponent's goal. The players competed with similar frequencies on both defence (114 duels on average with 51% accuracy) and attack (113 duels on average with 52% accuracy). The players of the elite football teams exhibited high performance efficiencies in the 1-on-1 duels, especially on their own half of the field and during the early stages of both halves of the match. The accuracy of duels of their performances decreased when the action moved closer to the opponent's goal and with the time in the game. ABSTRACT FROM AUTHOR